The Accuracy of Systemic Inflammatory Indices as Preeclampsia Markers: A Retrospective Study - Harvey Alvin Hartono; Pramudyo Dwiputro (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Objective: This study aimed to assess the association between systemic inflammatory indices, including the systemic immune inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), systemic inflammation response index (SIRI), and pan immune inflammation value (PIV), and the development of preeclampsia.Methods: A retrospective study was performed at a tertiary healthcare facility from January to June 2025. This study employed a cross sectional design involving 100 samples, divided into two groups: the preeclampsia group (n=50) and the control group (n=50). Hematological parameters and inflammatory indices were compared, with a p-value < 0.05 indicating statistical significance.Results: Normality tests, receiver operating characteristic (ROC) curve analyses, and correlation tests were conducted to evaluate the systemic immune index (SII), neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), systemic inflammation response index (SIRI), and pan immune inflammation value (PIV). Both the correlation test and ROC curve analyses showed no significant results for any variable (p > 0.05), with sensitivity and specificity ranging from 50 – 56% and 36 – 62%, respectively.Conclusion: The preeclampsia group tended to have higher inflammatory parameters, but the differences were not statistically significant. Future research could include additional inflammatory markers, such as CRP and fibrinogen, and consider confounding factors for more accurate results.Akurasi Indeks Inflamasi Sistemik Sebagai Penanda Preeklamsia: Sebuah Studi RetrospektifAbstrakTujuan: Penelitian ini bertujuan untuk menilai hubungan antara indeks inflamasi sistemik yaitu systemic immune-inflammation index (SII), neutrophil to lymphocyte ratio (NLR), monocyte to lymphocyte ratio (MLR), systemic inflammation response index (SIRI), dan pan immune inflammation value (PIV) dengan kejadian preeklampsia.Metode: Studi restropektif dilakukan di fasilitas kesehatan tersier periode Januari – Juni 2025. Metode penelitian yang digunakan dalam penelitian ini adalah cross-sectional. Studi ini meliputi 100 sampel, dibagi menjadi 2 kelompok: grup preeklamsia (n=50) dan kontrol (n=50). Parameter hematologi dan indeks inflamasi dibandingkan untuk dianalisis dengan nilai p< 0,05 dianggap signifikan secara statistik. Hasil: Uji normalitas, receiver operating characteristics (ROC) curve, dan uji korelasi dilakukan untuk menganalisis systemic immune index (SII), neutrophil to lymphocyte ratio (NLR), monocyte to lymphocyte ratio (MLR), systemic inflammation response index (SIRI), dan pan-immune inflammation value (PIV). Hasil uji korelasi dan ROC curve tidak menunjukkan hasil bermakna pada seluruh variabel (p> 0,05) dengan rentang sensitivitas dan spesifisitas masing-masing sebesar 50 – 56% dan 36 – 62%.Kesimpulan: Kelompok preeklamsia cenderung mempunyai parameter inflamasi lebih tinggi, tetapi tidak berbeda signifikan. Studi berikutnya dapat mengggunakan parameter inflamasi lebih banyak seperti CRP dan fibrinogen, dan menganalisis faktor perancu supaya hasil studi lebih akurat.